Peran Lembaga Pemberdayaan Masyarakat (LPM) Dalam Meningkatkan Perekonomian Masyarakat Di Kelurahan Penkase Oeleta Kecamatan Alak Kota Kupang - Kretisana Jagi (Jurnal Administrasi Terapan, 2024)
The Community Empowerment Institute (LPM) is an organization that aims to strengthen the role of society in development, one of which is economic development. LPM functions as a forum for mobilizing and developing the potential and abilities of the community in developing the potential that exists in their area. Some of LPM's roles in economic development include community empowerment. LPM plays a role in empowering communities to understand, access and utilize various available resources. The temporary survey shows that the role of LPM in improving the community economy in Penkase Oeleta Subdistrict through activities in the economic sector has not been maximized. LPM as an institution formed by the government with the aim of improving community welfare is expected to be able to create training and community development activities, so that the community's economy can be further improved. The aim of the research is: to determine the role of Community Empowerment Institutions (LPM) in improving the community economy in Penkase Village. The research will take place from January-June 2023. The type of data is primary data, secondary data. Results obtained: LPM plays a strategic role in identifying local economic potential and designing programs aimed at improving community welfare. LPM has succeeded in increasing people's skills and knowledge in the fields of entrepreneurship, financial management and agricultural technology. LPM also plays a role in ensuring sustainable management of natural resources that benefits local communities